ESTIMATION OF BUILDING ENERGY MANAGEMENT TOWARD MINIMIZING ENERGY CONSUMPTION AND CARBON EMISSION - Parvin K.; Hafiz W.M.; Abdullah M.A.; Hannan M.A.; Salam M.A. (Penerbit Universiti Teknikal Malaysia Melaka, 2023)
Up to 20% of the worlds total energy is used for lighting. Thus, one of the available solutions for minimizing energy consumption is by using a smart lighting system. In the smart lighting system, the lights are calibrated according to space occupation and the surrounding natural lighting condition. Accordingly, this paper estimates the impact of using smart lighting systems on the amount of energy consumption and carbon emission reduction. Seven days electricity consumption in the building of the College of Engineering (COE) at the Universiti Tenaga Nasional (UNITEN) was collected from Facility Development & Management known as FDM; these data were then used for the estimation in this paper. Based on the calculated results, up to 85% energy saving, carbon emission reduction, and bill saving can be obtained using LED-based smart lighting system. 2020